Fatigue Crack Growth Under Constant and Variable Amplitude Loading at Semi-elliptical and V-notched Steel Specimens. (2015) - Simunek, David; Leitner, Martin; Maierhofer, Jürgen; Gänser, Hans-Peter
Abstract: An assessment of fatigue crack propagation in components and structures based on fracture mechanical approaches is fundamental to define periodic intervals for service inspections. This paper focuses on the investigation of flat specimens made of mild steel S355 with V-shaped and semi-elliptical notches under constant and variable amplitude fatigue loading to analyze the influence of load sequence effects on crack propagation in order to obtain information about the remaining service life of components. Depending on the load sequence, crack propagation may be accelerated, delayed or in some cases even stopped, which leads to beach marks within the area of fracture. Fractographic analyses of the tested specimens are carried out by light-optical microscopy to determine different crack propagation stages. Numerical and analytical linear-elastic fracture mechanics (LEFM) calculations based on two- and three-dimensional models are performed for constant and variable amplitude loads. All analytical assessments of the V-notched specimen illustrate conservative results compared to testing, and the numerical results match the experimental investigations well. The maximum deviation of results is observed at variable amplitude loading due to missing retardation effects for the LEFM calculations. Preliminary distortion measurements and application of strain gauges on semi-elliptical notched specimens are performed to investigate the influence of angular deformation due to clamping on the local stress distribution. A simple model accounting for superimposed static bending stresses due to clamping is able to improve the crack growth predictions for semi-elliptical surface cracks significantly. A final comparison of the fractographic analyses and the numerical crack propagation calculations illustrates differences in the results and provides information to assess the fatigue crack growth and service inspection intervals of components under variable amplitude loading more precisely.